INCIDENCE OF UTERINE TORSION AND ITS OCCURRENCE IN RELATION TO VARIOUS FACTORS IN COWS AND BUFFALOES - KARTHICK, C; SELVARAJU, M; NAPOLEAN, R E; DORAISAMY, K A (The Indian Journal of Animal Reproduction, 2023)
Out of 852 dystocias analysed, the percentage of incidence of uterine torsion in cows and buffaloes was 13.97 and 27.46. The occurrences of uterine torsion in cows and buffaloes in response to parity (19.83 and 31.53 per cent in primiparous and 80.17 and 68.47 per cent in pleuriparous), stage of gestation (91.60 and 92.31 per cent in peripartum and 8.40 and 7.69 per cent in prepartum), side of torsion (72.34, and 91.61 per cent in right side and 27.66 and 8.39 per cent in left side), site of torsion (32.98 and 14.19 per cent in precervical and 67.02 and 85.81 per cent in postcervical), sex of fetus (67.57 and 60.55 per cent in male fetus and 32.43 and 39.45 per cent in female fetus) and livability (45.95 and 46.79 per cent in live fetuses and 54.05 and 53.21 per cent in dead fetuses, respectively) were recorded. The survivability of dam after detorsion in cows, buffaloes and overall survivability was 86.55, 88.46 and 87.82 per cent, respectively. About 49.1 O per cent cows and 51.52 per cent buffaloes were affected with 90° to 180° uterine torsion.